Essential role of TGF-beta/Smad pathway on statin dependent vascular smooth muscle cell regulation. - Juan Rodríguez-Vita (Public Library of Science (PLoS), 2008)
Background The 3-hydroxy-3-methylglutaryl CoA reductase inhibitors (also called statins) exert proven beneficial effects on cardiovascular diseases. Recent data suggest a protective role for Transforming Growth Factor-beta (TGF-beta) in atherosclerosis by regulating the balance between inflammation and extracellular matrix accumulation. However, there are no studies about the effect of statins on TGF-beta/Smad pathway in atherosclerosis and vascular cells. Methodology In cultured vascular smooth muscle cells (VSMCs) statins enhanced Smad pathway activation caused by TGF-beta. In addition, statins upregulated TGF-beta receptor type II (TRII), and increased TGF-beta synthesis and TGF-beta/Smad-dependent actions. In this sense, statins, through Smad activation, render VSMCs more susceptible to TGF-beta induced apoptosis and increased TGF-beta-mediated ECM production. It is well documented that high doses of statins induce apoptosis in cultured VSMC in the presence of serum; however the precise mechanism of this effect remains to be elucidated. We have found that statins-induced apoptosis was mediated by TGF-beta/Smad pathway. Finally, we have described that RhoA inhibition is a common intracellular mechanisms involved in statins effects. The in vivo relevance of these findings was assessed in an experimental model of atherosclerosis in apolipoprotein E deficient mice: Treatment with Atorvastatin increased Smad3 phosphorylation and TRII overexpression, associated to elevated ECM deposition in the VSMCs within atheroma plaques, while apoptosis was not detected. Conclusions Statins enhance TGF-beta/Smad pathway, regulating ligand levels, receptor, main signaling pathway and cellular responses of VSMC, including apoptosis and ECM accumulation. Our findings show that TGF-beta/Smad pathway is essential for statins-dependent actions in VSMCs.